(untitled) (Research, Society and Development, 2022)
This article aims to reflect on the place of storytelling in the integral formation process. Conceived as an active methodology, this practice, by allowing students to experience experiences that awaken the various human dimensions, contributes to the construction of knowledge in a meaningful learning process. For this reflection, we used exploratory research, which comprises the first stage of a broader investigation (Gil, 2008) and focuses on the reading of theoretical texts on the subject. The broader investigation, in this context, is a research carried out at the professional master’s level, whose product is a "Workshop Notebook" which suggests activities with storytelling aimed at high school students. After reading the theoretical framework, corresponding to the exploratory research, we concluded that storytelling as an active methodology contributes to the integral formation of students due to its humanized character, providing dynamism and creativity in the teaching and learning process.